2023
DOI: 10.5624/isd.20220173
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary sinus volumetric changes in jet aircraft pilots: A multislice computed tomography pilot study

Abstract: Purpose This study evaluated maxillary sinus volume changes in military jet aircraft pilot candidates before and after the training program, in comparison with a control group, considering the effects of pressurization, altitude, and total flight hours, through multislice computed tomography. Materials and Methods Fifteen fighter pilots were evaluated before initiating the training program and after the final approval. The control group consisted of 41 young adults who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It contributes to facial growth, reduction of skull weight, and absorption of traumatic impacts on cranial skull structures [ 8 ]. At 8-12 years of age, the maxillary sinus reaches its full size and stabilizes after the eruption of the maxillary second molar [ 9 , 10 ]. At approximately 20 years of age, pneumatization of the maxillary sinus ceases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It contributes to facial growth, reduction of skull weight, and absorption of traumatic impacts on cranial skull structures [ 8 ]. At 8-12 years of age, the maxillary sinus reaches its full size and stabilizes after the eruption of the maxillary second molar [ 9 , 10 ]. At approximately 20 years of age, pneumatization of the maxillary sinus ceases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have suggested that biomechanical stimulation has dimensional and volumetric effects on maxillary sinus in adults [ 7 , 10 ], while other studies have reported less or minimal effects on maxillary sinus dimensions and volume [ 16 , 17 ]. However, the hypothesis remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…9 Previously, it was reported that jet aircraft pilots have volume alterations in maxillary sinus, due to the exposition of diverse occupational hazards, such as high altitude and sudden movements, and multiple repetitive exposition to high gravitational force (Gz) changes. 10 However, the evaluation of paranasal sinuses for detecting inflammatory disease has not been studied in jet aircraft pilots.…”
Section: Introductionmentioning
confidence: 99%